Epidemiology of Campylobacter jejuni infections in Sweden, November 2011–October 2012: is the severity of infection associated with C. jejuni sequence type?. Issue 1 (1st January 2016) - Harvala, Heli; Rosendal, Thomas; Lahti, Elina; Engvall, Eva O.; Brytting, Maria; Wallensten, Anders; Lindberg, Ann
Abstract : Background: Campylobacter jejuni is among the most frequent causes of bacterial gastroenteritis in Europe. Over 8, 000 C. jejuni multilocus sequence typing sequence types (STs) have been described; ST-21 and ST-45 have been identified as the most frequent types in all human studies so far. In contrast to other STs, ST-22 has been associated with the Guillain–Barré syndrome and ST-677 was recently linked to severe systemic infections in Finland. We investigated risk factors associated with hospitalisation in individuals with C. jejuni infections acquired in Sweden. Methods: A total of 1, 075 individuals with domestically acquired C. jejuni infection diagnosed between November 2011 and October 2012 in Sweden were included in this retrospective cohort study. Typing data for the isolates as well as clinical data including hospitalisation dates and diagnosis codes for individuals with C. jejuni infection were obtained. Factors associated with hospitalisation and length of hospitalisation were investigated by multivariable analysis. Results: A total of 289 individuals were hospitalised due to C. jejuni infection (26.8%); those with co-morbidities were over 14 times more likely to become hospitalised than those without (odds ratio [OR]: 14.39, 95% confidence interval [CI]: 6.84–30.26). Those with underlying co-morbidities were also hospitalised longer than those without (4.22 days vs. 2.86 days), although this was not statistically significant. C. jejuni ST-257 (OR: 2.38; CI: 1.08–5.23), but not ST-22 or ST-677, was significantly associated with hospitalisation. Conclusion: ST-677 was not associated with increased hospitalisation or a longer hospital stay in our study whilst ST-257 was. However, individuals with C. jejuni infections were generally more frequently hospitalised than previously demonstrated; this requires further consideration including possible targeted interventions.